Pengaruh Geotekstil Terhadap Stabilitas Timbunan Jalan - Helmi Januar Hamzah; Sri Wulandari (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Infrastructure development, especially roads are closely related to geotechnical activities. The difference of contours at construction site forces embankment and excavation work. Embankment is an interesting thing to study more deeply because embankments have characteristics such as slopes that have safety factor and must be handled specifically. Geotextiles as an alternative to handling embankment stability are populary used for embankment construction. Many types of geotextile need to calculate and analyze in determining the type of geotextile that are suitable to the characteristics of the subgrade and embankment construction. Embankment stability analysis in this study was calculated using PLAXIS version 8.2 software and Mohr-Coulomb method as basic for calculation. Base on the result of this studie, use of geotextiles, whether woven, non-woven or geogrid, can increase the safety factor and accelerate consolidation time. There will be secondary consolidation consequence of the plastic adjustment of soil grains and geotextiles. The ideal of stress percentage for geotextile to be suitable for use is 56.957% - 37.194%.